HERMENEUTIKA SEBAGAI TEORI DAN METODE INTERPRETASI MAKNA TEKS SASTRA (Hermeneutics as Theory and Method of Interpretation of Literary Text Meaning) - Anshari Anshari (SAWERIGADING, 2009)
This analysis intends to describe theory and method of interpretation of literary text meaning, namely hermeneutic. Hermeneutic is interpreting process that involvesthree aspects such as, text, mediator, and reader. The three aspect relatedialectically and each aspects play role in process of giving meaning. Literary textis political symbol and consept so that it’s meaning is hidden. Hermeneutic is oneway to explore hidden meaning behind the literary text.